Corrosion Inhibition of Aluminium in Acidic Medium by Ethanol Leaf Extract of AzadirachtaIndica (Journal of Basic and Applied Research in Biomedicine, 2022)
The inhibition of aluminium corrosion in hydrochloric acid solution by ethanol leaf extract of Azadirachta indica was studied by weight loss and thermometric methods. Results obtained show that Azadirachta indica leaf extract leaf extract is a good inhibitor of aluminium corrosion in HCl solution. The inhibition efficiency increased with increase in Azadirachta indica leaf extract concentration but decreased with increase in temperature. The inhibition efficiencies by both weight loss and thermometric methods followed the same trend. The calculated thermodynamic parameters revealed that the adsorption of Azadirachta indica leaf extract onto aluminium surface occurred spontaneously and conformed to the Langmuir adsorption isotherm.